1998
DOI: 10.1093/ndt/13.3.570
|View full text |Cite
|
Sign up to set email alerts
|

Intoxication by star fruit (Averrhoa carambola) in six dialysis patients? (Preliminary report)

Abstract: We observed six cases of patients in a dialysis programme who were apparently intoxicated by ingestion of star fruit. After ingestion of 2-3 fruits or 150-200 ml of the fruit juice, the six patients, who had previously been stable in a regular dialysis programme, developed a variety of symptoms ranging from insomnia and hiccups to agitation, mental confusion and (in one case) death. In preliminary investigations to characterize the hypothetical neurotoxin in the fruit, an extract, when injected intraperitoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 0 publications
1
51
1
5
Order By: Relevance
“…These neurological events can be treated only by submitting the patients to hemodialysis. In spite of this therapeutic effort, many cases show a poor outcome which result in death (8)(9)(10). A water-soluble neurotoxin was isolated from star fruit (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These neurological events can be treated only by submitting the patients to hemodialysis. In spite of this therapeutic effort, many cases show a poor outcome which result in death (8)(9)(10). A water-soluble neurotoxin was isolated from star fruit (11).…”
Section: Introductionmentioning
confidence: 99%
“…A water-soluble neurotoxin was isolated from star fruit (11). This protein induced convulsion in rats by acting on Lglutamate release, as demonstrated in synaptosomes prepared from the rat cerebral cortex (8). These clinical and experimental effects motivated us to test some of the A. carambola extracts on the mammalian heart because folk medicine extensively uses teas and infusions obtained from carambola leaves.…”
Section: Introductionmentioning
confidence: 99%
“…In a study, Neto MM, Robl F, Netto JC, 1998 showed that six patients in a dialysis programme who were apparently intoxicated by ingestion of star fruit. After ingestion of 2-3 fruits or 150-200 ml of the fruit juice, the six patients who had previously been stable in a regular dialysis programme, developed a variety of symptoms ranging from insomnia and hiccups to agitation, mental confusion and (in one case) death 12 . Preliminary investigations to characterize the hypothetical hypothetical neurotoxin in the fruit, an extract, when injected intraperitoneally or intra-cerebroventricularly in rats, Clen CL et al, 2001, showed in their study that two of the patients developed nausea, vomiting, abdominal pain and backache within hours of ingestion of large quantities of sour carambola juice, then acute renal failure followed.…”
Section: Discussionmentioning
confidence: 99%
“…Single voxel protein and 31phosphorus MR spectroscopic studies revealed elevation of lactate, elevation of inorganic phosphate and reduced provoked persist convulsions of the tonic-clonic type. It appears that star fruit contains an excitatory neurotoxin 12 . Other reports have since confirmed these changes in CKD patients on and off dialysis 7,13 .…”
Section: Mechanism Of Star Fruit Induced Status Epilepticusmentioning
confidence: 99%
“…Therefore, the toxicity of star fruit in severe chronic kidney disease (CKD) patients has mainly been reported from Brazil and Taiwan. [3][4][5][6][7] In uremic patients, star fruit can cause various toxic effects including hiccups, vomiting, asthenia, paresis, muscle twitching, insomnia, mental confusion, convulsion, and coma. [3][4][5][6][7] The mortality rate after star fruit intoxication is as high as 20%-40% despite treatment with hemodialysis (HD) or supportive care.…”
mentioning
confidence: 99%